Remediation of a synthetic textile wastewater from polyester-cotton dyeing combining biological and photochemical oxidation processes - Vítor J. P. Vilar (2017)
This study reports an integrated treatment strategy for synthetic polyester-cotton dyeing wastewater, combining biological and photochemical oxidation processes. The biodegradability of all constituents, dyes and dyeing auxiliary products, present in the synthetic polyester dyeing textile wastewater were firstly analysed through a Zahn-Wellens test. More than 80% of the constituents are easily biodegradable, being possible to achieve its complete removal by biological oxidation. Consequently, the synthetic wastewater was firstly subject to a biological oxidation, achieving a dissolved organic carbon (DOC) removal of 76%, resulting in a bio-treated wastewater with 84 mg L-1 of DOC. The colour reduction was less than 5% Platinum-Cobalt Scale (Pt-Co scale), 9% (DFZ(436nm)), 3% (DFZ(525nm)) and 0% (DFZ(620nm)), (DFZ - DurchsichtFarbZahl, visual colour number in German). Thus, UVC/H2O2 and photo-Fenton (PF) oxidation processes were used as a polishing step for the decolourisation of bio-treated textile wastewater. The PF reaction did not promote wastewater decolourisation as shown by the colour indicators monitored. Moreover, the addition of oxalic acid did not result in an enhancement of the PF reaction. On the other hand, the photolysis of hydrogen peroxide using UVC radiation showed decolourisation efficiencies of 71% (Pt-Co method), 86% (DFZ(436nm)) and 97% (DFZ(525nm)) and more than 40% of mineralisation, consuming 14.1 mM H2O2 and 3.1 kJ(UVC) L-1 of energy dosage (time = 95 min; 6 W UVC lamp; natural pH = 8.4; T = 30 degrees C). The effect of hydrogen peroxide dosage, lamp power, solution pH and temperature on the UVC/H2O2 efficiency for wastewater decolourization was evaluated. During the photochemical reaction some low-molecular-weight carboxylic acids were detected, as oxalic acid, maleic acid and tartaric acid. The integrated treatment strategy was able to achieve a wastewater quality in agreement with the discharge limits imposed by legislation, and the total operating costs was 2.33 (sic) m(-3).